Innovation in craft products and performing arts through community empowerment in Sukaluyu Village - Juju Masunah; Reni Haerani; Fitri Rahmafitria; Agus Ahmad Wakih (Universitas Pendidikan Indonesia, 2026)
The development of culture-based tourism villages still faces obstacles to integrating artistic potential into the tourism system and creating sustainable economic value. One alternative that can be implemented is educational tourism arts that combine elements of art, education, and tourist participation in an integrative empowerment model. The objective of this activity is to develop innovative bamboo woven craft products and Angklung Sered performances as tourist attractions in Sukaluyu Village. The method used is community-based participatory research. Partners involved in this activity are the Sered Angklung Studio and the village's Youth Organization. The activity stages include partner determination, problem identification, needs mapping, innovation formulation, program socialization, training, technology implementation, mentoring, and evaluation. The results of the activity indicate that the Sered Angklung Studio can produce educational tourism arts innovations that are more participatory, concise, interactive, and engaging, and that contain educational value. Meanwhile, the Youth Organization developed miniature traditional kitchen utensils as a learning medium based on local wisdom, with both educational and economic value. These two innovative products were then integrated into the development of the pilot tourism village. In addition to producing innovative cultural products, this activity strengthens the role of cultural education, expands community participation, and creates new economic opportunities for residents. Abstrak Pengembangan desa wisata berbasis budaya masih menghadapi kendala dalam mengintegrasikan potensi seni ke dalam sistem pariwisata serta menciptakan nilai ekonomi yang berkelanjutan. Salah satu alternatif yang dapat diterapkan adalah seni wisata pendidikan yang menggabungkan unsur seni, edukasi, dan partisipasi wisatawan dalam model pemberdayaan yang integratif. Tujuan kegiatan ini adalah untuk mengembangkan inovasi produk kerajinan anyaman bambu dan pertunjukan Angklung Sered sebagai atraksi wisata di Desa Sukaluyu. Metode yang digunakan adalah community-based participatory research. Mitra yang dilibatkan dalam kegiatan ini adalah Sanggar Angklung Sered dan Karang Taruna desa. Tahapan kegiatan mencakup penetapan mitra, identifikasi persoalan, pemetaan kebutuhan, perumusan inovasi, sosialisasi program, pelatihan, penerapan teknologi, pendampingan, serta evaluasi. Hasil kegiatan menunjukkan bahwa Sanggar Angklung Sered mampu menghasilkan inovasi seni wisata pendidikan yang lebih partisipatif, ringkas, interaktif, menarik, dan mengandung nilai-nilai pendidikan. Sementara itu, Karang Taruna mengembangkan miniatur perkakas dapur tradisional sebagai media pembelajaran berbasis kearifan lokal yang memiliki nilai edukatif sekaligus nilai ekonomi. Kedua produk inovasi tersebut kemudian diintegrasikan sebagai bagian dari pengembangan desa wisata rintisan. Selain menghasilkan inovasi produk budaya, kegiatan ini turut memperkuat fungsi edukasi budaya, memperluas partisipasi masyarakat, serta membuka peluang ekonomi baru bagi warga setempat. Kata Kunci: Angklung Sered; kerajinan; pemberdayaan masyarakat; seni wisata pendidikan